Alimentary 'green' proteins as electrospun scaffolds for skin regenerative engineering. (12th April 2012) - Lin, Leko; Perets, Anat; Har‐el, Yah‐el; Varma, Devika; Li, Mengyan; Lazarovici, Philip; Woerdeman, Dara L.; Lelkes, Peter I.
Abstract As a potential alternative to currently available skin substitutes and wound dressings, we explored the use of bioactive scaffolds made of plant‐derived proteins. We hypothesized that 'green' materials, derived from renewable and biodegradable natural sources, may confer bioactive properties to enhance wound healing and tissue regeneration. We optimized and characterized fibrous scaffolds electrospun from soy protein isolate (SPI) with addition of 0.05% poly(ethylene oxide) (PEO) dissolved in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol, and from corn zein dissolved in glacial acetic acid. Fibrous mats electrospun from either of these plant proteins remained intact without further cross‐linking, possessing a skin‐like pliability. Soy‐derived scaffolds supported the adhesion and proliferation of cultured primary human dermal fibroblasts. Using targeted PCR arrays and qPCR validation, we found similar gene expression profiles of fibroblasts cultured for 2 and 24 h on SPI substrates and on collagen type I at both time points. On both substrates there was a pronounced time‐dependent upregulation of several genes related to ECM deposition remodelling, including MMP‐10, MMP‐1, collagen VII, integrin‐α2 and laminin‐β3, indicating that both plant‐ and animal‐derived materials induce similar responses from the cells after initial adhesion, degrading substrate proteins and depositing extracellular matrix in a 'normal' remodelling process. These results suggest that 'green' proteins, such as soy and zein, are promising as a platform for organotypic skin equivalent culture, as well as implantable scaffolds for skin regeneration. Future studies will determine specific mechanisms of their interaction with skin cells and their efficacy in wound‐healing applications. Copyright © 2012 John Wiley & Sons, Ltd.